THE EFFECT OF LAVENDER AROMATHERAPY ON SLEEP QUALITY AMONG ADOLESCENTS WITH SLEEP DISTURBANCES AT SMK MUHAMMADIYAH 07 GONDANGLEGI MALANG - Ayunda Aprilia; Nila Widya Keswara; Rifzul Maulina (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Sleep disorders in adolescents are common health problems that can affect physical health, emotional well-being, and learning ability. One non-pharmacological therapy that can be used to help improve sleep quality is lavender aromatherapy, which has a relaxing effect on the nervous system. This study aimed to determine the effect of lavender aromatherapy on sleep quality among adolescents at SMK Muhammadiyah 7 Gondanglegi. This study used a pre-experimental design with a one group pretest - posttest approach. The population in this study consisted of 60 twelfth-grade nursing students at SMK Muhammadiyah 7 Gondanglegi, while the sample included 43 respondents selected using purposive sampling technique. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI) questionnaire before and after the intervention of lavender aromatherapy for seven days. Data were analyzed using the paired sample t-test with a significance level of α = 0.05. The results showed that the mean PSQI score before the intervention was 12.35, while after the intervention it decreased to 5.23, indicating an average reduction of 7.12 points. The statistical test showed a p-value = 0.000 (p < 0.05), which means that there was a significant effect of lavender aromatherapy on improving adolescents' sleep quality. Based on these results, it can be concluded that lavender aromatherapy has an effect on improving sleep quality in adolescents and can be used as a non-pharmacological alternative therapy to help overcome sleep disorders.